COVD-06. BRAIN TUMOURS AND COVID-19: THE PATIENT AND CAREGIVER EXPERIENCE. (9th November 2020) - Voisin, Mathew; Oliver, Kathy; Farrimond, Stu; Chee, Tess; ,; Zadeh, Gelareh
Abstract: BACKGROUND: Since the COVID-19 pandemic, thousands of medical procedures and appointments have been cancelled or delayed. The long-term effects of these drastic measures directly on brain tumour patients and their caregivers are unknown. The purpose of this study is to better understand how COVID-19 has affected this vulnerable population on a global scale. METHODS: An online 79-question survey was developed by the IBTA, in conjunction with the SNO COVID-19 Task Force. The survey was sent to over 120 brain tumour charities and not-for-profits worldwide and disseminated to brain tumour patients and caregivers. All responses were subdivided by patient vs caregiver and by geographical region. RESULTS: In total, 1989 participants completed the survey from 33 countries, including 1459 patients and 530 caregivers. There were no significant differences in COVID-19 testing rates (p = 0.662) or the number of positive cases for brain tumour patients between regions (p = 0.1068). Caregivers were significantly more anxious than patients (p = < 0.0001). Patients from the Americas were most likely to have lost their jobs due to the pandemic, practiced self-isolation, and received telehealth services (p = < 0.0001). Patients from Europe experienced the most treatment delays (p = 0.0031). Healthcare providers were ranked as the most trusted source of information. CONCLUSIONS: As a result of COVID-19, brain tumour patients and caregivers have experienced significant stress and anxiety. Healthcare professionals, brain tumour charities, and not-for-profits must ensure that they continue to provide accessible, high-quality care, information, and support in the age of COVID-19.